Paternal effects without paternity? Testing non-genetic male influence on offspring size and brood size in a gynogenetic vertebrate, the Amazon molly (Poecilia formosa) - Ulrike Scherer; Sean M. Ehlman; David Bierbach; Jens Krause; Max Wolf (PLoS ONE, 2026)
Paternal effects, i.e., effects of fathers on the phenotype of their offspring that are not mediated by the transmission of alleles, are increasingly recognized as a potentially significant source of phenotypic variation across taxa – even in the absence of paternal care. Gynogenetic systems, which rely on sperm to trigger embryogenesis without incorporating male genetic material, provide a powerful way to experimentally isolate paternal effects from effects caused by the integration of male genetic material. Up to now, however, paternal effects remain largely unexplored in these systems. Here, we tested for non-genetic paternal effects in the gynogenetic Amazon molly ( Poecilia formosa ): a naturally clonal, all-female species with no parental care. Using a highly controlled breeding experiment involving 60 Atlantic molly males ( Poecilia mexicana ) and 54 Amazon molly females from a single clonal lineage, we generated 128 broods and 2,435 offspring. While males were drawn from a naturally variable stock population, females – next to being genetically identical – were standardized for age, size, descent, and developmental experience. We asked whether male identity or body size predicted offspring size – a key offspring phenotypic trait. We also asked whether male identity or body size predicted brood size. Male identity explained either no or only very small proportions of the variation in offspring or brood size. Larger males were weakly associated with larger offspring, but this effect was minimal (partial R 2 ~ 1.5%). However, these patterns did not hold consistently across all data exclusion criteria and analytical variants, underscoring their tentative nature and highlighting the need for further investigation. Our study offers one of the first empirical tests of male effects in a gynogenetic vertebrate, providing valuable quantitative benchmarks for the magnitude of such effects in gynogenetic systems.